2005
DOI: 10.1111/j.1447-0756.2005.00323.x
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis and management for a large fetal cardiac tumor complicated with hydrops fetalis

Abstract: Fetal cardiac tumor is a rare disease, and its prognosis varies in relation to the complications such as arrhythmia and out-flow obstruction. Hydrops fetalis is one of severe complications that result in an unfavorable outcome. A case is presented herein of a large fetal cardiac tumor diagnosed at 28 weeks gestation. At 30 weeks gestation, the fetus complicated with hydrops fetalis because of impaired cardiac function. Increased peak systolic velocity in the ascending aorta and marked reversed flow in the duct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…Also excluded were studies in which individual background data or outcomes for the cases in the study were not reported. Clinical findings, imaging studies, pathology reports and outcomes of 64 case reports or small case series with cardiac rhabdomyomas were reviewed, tabulated and discussed1–8, 13–68.…”
Section: Methodsmentioning
confidence: 99%
“…Also excluded were studies in which individual background data or outcomes for the cases in the study were not reported. Clinical findings, imaging studies, pathology reports and outcomes of 64 case reports or small case series with cardiac rhabdomyomas were reviewed, tabulated and discussed1–8, 13–68.…”
Section: Methodsmentioning
confidence: 99%
“…In the case of increasing circulatory failure, such as cardiomegaly, ascites, or pleural effusion, an attempt to improve myocardial contractility may be considered by transplacental digoxin treatment, but in our material of 37 cases, it was not necessary [10,20,21]. In cases of single tumours, which progressively increase their mass, in developing fetal circulatory failure, surgical treatment should be considered prenatally or in the first days of the newborn's life.…”
Section: Discussionmentioning
confidence: 97%
“…Nakata et al [36] described a pregnant woman who was evalu ated for a fetal cardiac mass at 28 weeks' gestation, and hydrops fetalis developed at 30 weeks' gestation. Maternal medication with digoxin was started and the elevated preload condition was slight ly improved at 34 weeks' gestation.…”
Section: Cardiac/pericardial Tumorsmentioning
confidence: 99%
“…In utero fetal therapy or preterm delivery should be considered if cardiac function is severely impaired [36]. The aim of in utero in tervention for hydrops fetalis is to avoid adverse fetal events and to prolong gestation time for expected fetal lung maturation.…”
Section: Managementmentioning
confidence: 99%